Four scenarios of environmental risk of diclofenac in European groundwater ecosystems. (15th October 2021) - Di Lorenzo, T.; Cifoni, M.; Baratti, M.; Pieraccini, G.; Di Marzio, W.D.; Galassi, D.M.P.
Abstract: Groundwater is the largest source of liquid freshwater on Earth. Groundwater ecosystems harbor a rich biodiversity, mainly consisting of microbes and invertebrates that provide substantial ecological services. Despite its importance, groundwater is affected by several anthropic pressures, including pollution from pharmaceutical compounds. Diclofenac is the non-steroidal drug most widely detected in freshwaters, both in surface waters (e.g., rivers, streams, lakes etc.) and groundwaters. Unlike surface waters, the environmental risk of diclofenac in European groundwaters has not yet been assessed by the competent Authorities. The environmental risk assessment refers to the analysis of the potential risk that a chemical compound poses to a given environment by comparing its measured environmental concentrations to its predicted no-effect concentration. In this study, we explored four environmental risk scenarios in European groundwaters using different methodologies. We obtained diverse risk expectations, some indicative of a moderately diffuse environmental risk for concentrations of diclofenac ≥42 ng/L and others indicative of a widespread environmental risk for concentrations ≥5 ng/L. The difference among the four scenarios mainly related to the methods of calculating the predicted no-effect concentration of diclofenac. We discussed the four scenarios in order to identify the most realistic risk expectations posed by diclofenac to European groundwater ecosystems. Graphical abstract: Image 1 Highlights: Four scenarios of environmental risk of diclofenac in EU groundwater are presented. Scenarios#1 and #2 depicted a widespread risk for MECs≥5 ng/L of diclofenac. Scenarios#3 and #4 depicted a moderately diffuse risk for MECs≥42 ng/L diclofenac. The differences among the scenarios are due to the methods of PNECGW computation. Abstract : The study explored four different environmental risk scenarios of diclofenac in European groundwaters using different methodologies.